Changes in Residual Alveolar Ridge Following Tooth Extraction & the Necessity of Placing Bone Graft Material in the Extracted Socket to Prevent Bone Resorption - A Review Article (Bangladesh Journal of Dental Research & Education, 2013)
Bangladesh Journal of Dental Research & Education, Vol. 01, No. 01, January 2011, Page 30-32 DOI: http://dx.doi.org/10.3329/bjdre.v1i1.15800